Standaarde vir prestasiebeoordeling van akademiese personeel aan 'n verplegingskollege - H. Aucamp; Marie Muller (AOSIS, 2000)
The purpose with this research is to formulate standards for performance appraisal of academic staff within a nursing college. A qualitative exloratory and descriptive research strategy was utilised, within the context of Gauteng nursing colleges. The conceptual framework on which the standards are based, was developed by exploring and describing existing job descriptions of academic staff (Chief Professional Nurse) employed in nursing colleges, as well as the expectations of academic staff regarding performance appraisal in the college. These results were exposed to a literature control prior to the writing of final statements and a conceptual framework for the formulation of these standards. The standards are divided into three main dimensions, viz. the organisational climate within the nursing college, the purpose of performance appraisal and finally the process of performance appraisal. It is recommended that these standards be implemented in nursing colleges and exposed to further validity studies.